LA PRASSI DIDATTICA DELL’ITALIANO PER SCOPI SPECIALI NELL’AMBITO UNIVERSITARIO POLACCO SULL’ESEMPIO DELLA VARIETÀ MEDICA - Szpingier, Beata Katarzyna (Neofilolog, 2019)
The present analysis aims at systematizing sparse remarks revolving around teaching of languages for special purposes (LSP). Detailed data were collected by observation within Polish academic circles. More precisely, they are based on past working experience gained among stu-dents boasting a high level of language proficiency. Apart from general tendencies, more streamlined requirements have been formulated on a par with their particular consequences.